(untitled) (Fiep Bulletin - online, 2013)
Currently the electronic gaming consoles have been used in physical rehabilitation programs. With the Nintendo Wii Fit® system can develop a training protocol aimed at improving postural control and control of weightbearing between members. The objective of this pilot study was to determine the pattern of displacement of the center of pressure (CP) of subjects who underwent a 10 minute workout in a gameterapia to present the alternative training weight discharges through games in virtual reality. For both 16 volunteers underwent two evaluations, one before any familiarity with the game Tilt Table® games belonging to Nintendo Wii® console and another after 10 minutes of training. During the evaluations, the training tool (Wii Balance Board®) was placed on the force platform to collect data concerning the pattern of displacement of the center of pressure in the first 4 levels of difficulty of the game. The data described were the anterior-posterior and medial-lateral. As a result shows that the subjects have explored its support base by means of displacement of CP during the execution of the task, moreover, by means of offset values ??of the pressure center can perform a quantitative analysis of the training participants, which indicates that it is feasible to train discharges weight using the Wii Fit® system in the laboratory, thus tracking the performance of patients who undergo this type of intervention.